BP « Deepwater Horizon » du Golfe du Mexique à l’Afrique : un tournant pour l’industrie pétrolière ? - Géraud Magrin; Bopp van Dessel (EchoGéo)
On Thursday the 20th april 2010, the blowout of the Deepwater Horizon drilling platform operated by BP in the Gulf of Mexico starts what can be considered one of the major oil spills in the world history. Taking place in the national waters of the world’s first oil consumer and affecting one of the more advanced oil major in Corporate Social Responsibility, this accident may turn out to be a land mark for environmental management in the sector. International Oil Companies are pushing the (technical/managerial) borders to stay in business in modern world (with the State Oil Companies doing the easy oil left) and provide us the oil we are addicted to. The exploration of oil and gas in Deepwaters or extreme environments brings along new and increased risks. The BP accident shows that a small risk is never zero: there should have been a trustworthy plan B, but there was none. Also, we realize that we do not understand a lot of the behaviour and potential impacts of oil in (deeper) water as long as it does not surface or ends up on the beach. However, it is more and more recognised that this major Deepwater accident will have strong and long lasting pelagic effects. This event will likely change the game worldwide concerning environmental precautions for oil and gas in sensitive circumstances. We give a brief insight of these issues in Africa, particularly in Mauritania, where similarly ambitious off shore operations are being implemented in an area with high economic and nature values and ecological sensitivities. But as these precautions will make the oil more expensive, it could also contribute to speed the transition to a more sustainable world energetic matrix.